Medical Fruits of Labor. (August 2015) - Isaacs, Michael
My grandfather's death made a profound impact on my life personally and professionally. Our family was able to share in his last joyous days thanks to a caring physician who first suggested palliative care. During these final days in which friends and family said their goodbyes, I realized as a medical student the immense impact we as healthcare workers truly make in our patients' lives. Reflections on palliative care, faith, medicine, and death following this experience influenced my formation as a Catholic, grandson, and as a physician in training. Lay summary: This article describes the personal experience of a medical student who witnesses the final days of his grandfather's life. Life, death, faith, palliative care, and the impact of physicians on families during these times is the subject of his reflection following his grandfather's death.